The “PARTHENOS eHumanities and eHeritage Webinar Series”: Webinars as a means to deliver successful research infrastructure training - Wuttke, Ulrike (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Research infrastructures have an ever greater presence in both the Humanities and Cultural Heritage Studies. Scholars and information professionals working in the fields of research libraries, archives, and information play a crucial role as users and providers in cultivating the kind of world-class research that today increasingly relies on the use of these digital research infrastructures. Therefore, their continuous professional development is essential for them to be able to reap the benefits available from the ever-changing field of eHumanities and eHeritage research infrastructures, a mission that is at the heart of the Training team of the Horizon 2020 funded project PARTHENOS (“Pooling Activities, Resources and Tools for Heritage e-Research, Optimization and Synergies”).This paper describes the “PARTHENOS eHumanities and eHeritage Webinar Series”. These five live and interactive seminars delivered via the internet represent an introductory training programme that focuses on the professional development and capacity building needs and requirements of (digital) humanities and cultural heritage scholars, as well as of information specialists who work for digital humanities and digital heritage infrastructures. Using the PARTHENOS Webinar Series as a case study of the development and delivery of research infrastructure-focussed professional development, the paper outlines the intellectual, educational, and practical context in which the PARTHENOS Webinar Series was conceived, the syllabus used for the initial run of the series, and the analysis of the data collection exercises conducted after the first five webinars, especially the feedback collected from both the trainees and the trainers (online survey and open questions study), and it discusses possibilities for improvement. In the conclusion, the paper places the insights from the PARTHENOS webinars in the context of the potential of webinars for research infrastructure training. It argues that in order to reap their full potential for research infrastructures as training instrument as well as instruments to gain insights in user requirements, new developments, and for community building, further theoretical grounding, professionalization, and on-going analysis of their effectiveness is needed.